MonoMax Suture: A New Long-Term Absorbable Monofilament Suture Made from Poly-4-Hydroxybutyrate - Erich K. Odermatt; Lutz Funk; Rainer Bargon; David P. Martin; Said Rizk; Simon F. Williams (International Journal of Polymer Science)
A long-term absorbable monofilament suture was developed using poly-4-hydroxybutyrate (P4HB) made from a biosynthetically produced homopolymer of the natural metabolite 4-hydroxybutyrate. The suture, called MonoMax, has prolonged strength retention. At 12 weeks, a size 3-0 MonoMax suture retains approximately 50% of its initial tensile strength in vivo and is substantially degraded in one year with minimal tissue reaction. In contrast, PDS II monofilament suture (Ethicon, Inc., Somerville, NJ) has no residual strength in vivo after 12 weeks. In vivo, the MonoMax suture is hydrolyzed primarily by bulk hydrolysis, and is then degraded via the Krebs cycle. MonoMax is substantially more compliant than other monofilament sutures, and incorporates an element of elasticity. Its tensile modulus of 0.48 GPa is approximately one-third of the value of the PDS II fiber providing an exceptionally flexible and pliable fiber with excellent knot strength and security. These features are further enhanced by the fiber's elasticity, which also improves knot security and may help prevent wound dehiscence. Because of its performance advantages, this suture may find clinical utility in applications where prolonged strength retention, and greater flexibility are required, particularly in procedures like abdominal wall closure where wound dehiscence is still a significant post-surgical complication.